Design and implementation of an intensive panel survey with refugees and other migrants in need of protection in Costa Rica. - Abigail Weitzman; Matthew Blanton; Sophie M Morse; Gilbert Brenes Camacho; María José Chaves Groh (PLoS ONE, 2024)
Over the last decade, the global population of refugees and other migrants in need of international protection (MNP) has more than doubled. Despite their rapid growth, panel data collection among MNP remains rare, leaving scholars with few data sources to draw on to understand dynamic changes in their social, economic, legal, or health circumstances. With that paucity in mind, we developed and piloted the Encuesta de Refugiados: Experiencias Sociales y Salud (ERESS), a weekly panel survey conducted with MNP living in Costa Rica. To our knowledge, this panel constitutes one of the first weekly surveys with MNP anywhere in the world. Here, we describe the overall study design, sample recruitment and retention, and key descriptive findings. We show that retaining demographically and socioeconomically diverse MNP in intensive panel surveys is possible and that doing so reveals valuable insights into dynamic changes in their incorporation, family dynamics, and health and wellbeing. By offering a summary of our field experiences and central methodological findings, we highlight the potential benefits and challenges of collecting intensive panel data with MNP, as scholars increasingly seek to understand their pre- and post-migration trajectories and relationships between the two.